Compendium of school laws in the Philippines - Sarmiento, Ulpiano P. III ([Manila] Ulpiano P. Sarmiento III, 2015)
"This book is the compendium of education of laws in the Philippines into 3 separate volumes to reflect the development that the Commission on Higher Education (CHED), the Department of Education (DepEd) and the Technical Education and Skills Development Authority (TESDA). Each volume contains the most recent and complete compilation of the laws, rules, regulations, and decisions affecting Philippine Education. Among others, the Enhanced Basic Education Law or the K to 12 Law, the Anti-Bullying Law, the Universal Kindergarten Law as well as the landmark decisions of the Supreme Court until December of 2014, are included."--Preface.
Volume 1. The manual of regulation for private higher education ; A. General provisions ; B. The higher education system ; C. The Commission on Higher Education system ; D. Private Higher Education Institutions ; E. higher Education Programs ; F. Terms and conditions of employment ; G. Financial management and financial assistance ; H. Administrative Remedies ; I. Miscellaneous provisions. -- Volume 2. The revised manual of regulations for private schools in basic education ; I. General provision ; II. Basic education ; III. The Department of Education ; IV. Rules and regulations governing private schools in basic education.
Keywords: Educational law and legislation -- Philippines; Private schools -- Law and legislation -- Philippines; Private universities and colleges -- Law and Legislation -- Philippines